1992
DOI: 10.1001/archsurg.1992.01420090127019
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected, Late Cardiovascular Effects of Surgery for Peripheral Artery Disease

Abstract: In reviewing late morbidity of a multicenter clinical trial comparing balloon angioplasty (percutaneous transluminal angioplasty) with bypass surgery for lower-extremity ischemia, an unexpectedly high incidence of adverse systemic events in surgical patients was uncovered. The study was prospective and randomized, and included a total of 263 patients, with follow-up from 2 to 6 years. When end points of related deaths, amputations, and intervention failures were summed, surgery was favored over percutaneous tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…However, a multicenter prospective randomized study comparing percutaneous transluminal angioplasty with bypass surgery for lower extremity ischemia in the general population, the Veterans Affairs Cooperative Study 199, revealed considerably higher 5-year morbidity and mortality rates in patients undergoing surgical revascularization. In surgically treated patients, mortality was 13.1% per year, whereas it was 8.4% per year for patients treated with angioplasty [29].…”
Section: Discussionmentioning
confidence: 92%
“…However, a multicenter prospective randomized study comparing percutaneous transluminal angioplasty with bypass surgery for lower extremity ischemia in the general population, the Veterans Affairs Cooperative Study 199, revealed considerably higher 5-year morbidity and mortality rates in patients undergoing surgical revascularization. In surgically treated patients, mortality was 13.1% per year, whereas it was 8.4% per year for patients treated with angioplasty [29].…”
Section: Discussionmentioning
confidence: 92%
“…Prior studies suggest that major post-operative AEs portend a negative impact on later outcomes beyond the initial hospitalization. 6 ALI patients are at risk of a tumultuous post-operative course secondary to their poor medical optimization and the need for urgent revascularization, which is associated with longer and more complicated procedures with higher blood loss. 4-6,11,20 Certain subsets of ALI patients will likely have a greater benefit from one type of revascularization technique over another given the heterogeneity of ALI patients with variable etiologies, comorbidities, and physiologic reserve.…”
Section: Discussionmentioning
confidence: 99%
“…This subpopulation represents the most challenging of the ALI patients to treat given their advance disease and comorbidities placing them at the highest risk not only for postoperative complications, but limb loss and mortality beyond the initial perioperative period, with a 27% amputation rate and a 65% mortality rate at 5 years. 4-6,24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations